1996
DOI: 10.1016/0014-5793(95)01466-7
|View full text |Cite
|
Sign up to set email alerts
|

Murine and human mast cell express acetylcholinesterase

Abstract: Expression of catalytically active protein was detected in a murine mast cell line. The primary type of AChE mRNA produced by these cells was found to be the brain and muscle type by PCR amplification of alternative exons from the 3' of mast cells AChE cDNA. AChE was further found to be expressed in the HMC-1 the human mast cell precursor line. Furthermore, utilizing the single cell RT-PCR method we detected AChE mRNA expression in FcERI-positive single cells derived from human colonic mucosal biopsies. Our fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…13 MC mediators can sensitize sensory neurons, which further activate or inhibit the MC by releasing neurotransmitters or neuropeptides (eg, neurotensin, somatostatin, substance P, and acetylcholine), revealing another probable mode of molecular communication between MCs and neurons. 19,20 In addition, the MCs seem to play a crucial role in local mechanisms of pain control. The number of MCs within the endometrium is low, and those that are present are predominantly localized to the basal layer.…”
Section: Discussionmentioning
confidence: 99%
“…13 MC mediators can sensitize sensory neurons, which further activate or inhibit the MC by releasing neurotransmitters or neuropeptides (eg, neurotensin, somatostatin, substance P, and acetylcholine), revealing another probable mode of molecular communication between MCs and neurons. 19,20 In addition, the MCs seem to play a crucial role in local mechanisms of pain control. The number of MCs within the endometrium is low, and those that are present are predominantly localized to the basal layer.…”
Section: Discussionmentioning
confidence: 99%
“…Most isoforms are found in the central and peripheral nervous systems [Taylor and Radic, 1994;Soreq and Seidman, 2001]. Isoforms have also been characterized in hematopoietic cells, as well as in tumor cells [Karpel et al, 1994;Nechushtan et al, 1996;Perry et al, 2002]. The different isoforms have been shown by reverse-transcriptase polymerase chain reaction (RT-PCR) to result from alternative splicing of AChE mRNA leading to isoforms of AChE protein differing in their 3′ exon composition [Karpel et al, 1994;Perry et al, 2002].…”
mentioning
confidence: 99%
“…The importance of this to CNS disease has been reviewed by Theoharides et al 46 who observed that mast cells are primarily perivascular in the CNS. In other areas, mast cells show cholinesterase activity, which suggests that mast cell enzymatic reactions could depress cholinergic activity in localized areas of the brain 47 …”
Section: Mast Cellsmentioning
confidence: 99%